Efforts to Increase The Students' Level of Confidence in Mathematics Learning Using Numbered Head Together (NHT) Model - Zuida Ratih Hendrastuti (Indonesian Journal of Mathematics Education, 2019)
This study aims to improve the students’ confidence through the Numbered Head Together (NHT) learning model in learning mathematics in class VIII D of SMP N 3 Depok. This research is a classroom action research (CAR) using NHT model. The stages in this study consist of planning, action, observation, and reflection. The research subjects include 32 students. The data collection techniques used are a test, questionnaires, and observation. The data collection instruments used are written tests to measure the students’ cognitive learning outcomes, self-confidence questionnaire, and observation sheets to determine the feasibility of learning using the NHT technique. The data analysis technique uses percentages for the learning outcomes using observation sheets, data analysis of descriptive study completeness describing individual and group students’ outcomes, and scoring for self-confidence questionnaire using Likert scale with five criteria intervals. The results of the analysis of this research indicate that mathematics learning increases student confidence by 10.22%. The students’ outcomes (cognitive) have decreased, and one of them is the learning material that is more difficult than the cycle I. The basic competence for cycle I is to complete SPLDV (Sistem Persamaan Linear Dua Variabel) while for cycle II, the basic competence is to make and complete mathematical models of problems related to SPLDV. The implementation of learning using the NHT learning model has increased from 81.3% in the first cycle to 96.9% in the second one. It can be concluded that the NHT cooperative learning model is proven to improve the students’ confidence.